Additive Manufacturing of Biodegradable Metallic Implants by Selective Laser Melting: Current Research Status and Application Perspectives - Anna Gracheva; Igor Polozov; Anatoly Popovich (Metals, 2025)
Biodegradable metallic implants represent a paradigm shift in implantology, eliminating secondary removal surgeries through predictable controlled degradation. This review systematizes current achievements in selective laser melting (SLM) of biodegradable metals (Mg, Fe, Zn), analyzing how processing parameters influence microstructure, mechanical properties, and degradation kinetics. Key findings demonstrate that SLM-produced Mg alloys achieve bone-matching modulus (40–45 GPa) with moderate degradation (1–3 mm/year); Fe-based systems provide superior strength (400–600 MPa) but slower degradation (0.1–0.5 mm/year); while Zn alloys offer intermediate properties. Design strategies for porous/lattice structures enhancing osseointegration and enabling property gradients are discussed. Major challenges include controlling degradation kinetics, optimizing SLM parameters for reactive metals, standardizing testing methodologies, and regulatory harmonization. This comprehensive analysis provides systematic guidelines for material selection and process optimization, establishing a foundation for developing next-generation personalized biodegradable implants.